2017
DOI: 10.1108/jkm-01-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital management and power mobilisation in a seaport

Abstract: Purpose The purpose of this paper is to discuss how the management of collective intellectual capital (CIC) occurs in a seaport through the actions of the network coordinator. Design/methodology/approach A case study was conducted in a seaport, focusing on the actions taken by a network coordinator – a port authority – to develop the seaport’s CIC. The seaport is conceptualised as a meta-organisation, composed by interdependent actors which may possess different interests and different levels of power. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…He also mentioned the "interdependence" dimension, exemplifying it with the cost sharing regarding radio advertising, billboards, or the access to technologies such as the new CRM software. These perspectives are in line with [5], who suggest that collaboration can develop RC through trust, interdependence and participatory communication.…”
Section: Findings and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…He also mentioned the "interdependence" dimension, exemplifying it with the cost sharing regarding radio advertising, billboards, or the access to technologies such as the new CRM software. These perspectives are in line with [5], who suggest that collaboration can develop RC through trust, interdependence and participatory communication.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…Relationship management in collaborations is crucial for partners to maximise the likelihood of success [6]. Relational Capital can be developed through different dimensions such as trust, interdependence or participative communication [5]. The higher the level of such dimensions, the better the collaboration outcomes are likely to be [6].…”
Section: Inter-organisational Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…The power balance or imbalance between actors is also relevant. Vale et al [51] exemplify how coercive power is used in a situation with imbalance between actors, while resources to coerce were not available in another situation where there was power balance between the actors [52].…”
Section: Bases Of Powermentioning
confidence: 99%
“…This paper takes the perspective, in line with, e.g., [27,28,53], that power and trust can co-exist. Vale et al [52], for example, found the use of non-coercive types of power to foster trust between stakeholders. The coexistence of power and trust also opens up for the use of trust as a mediating mechanism to decrease effects of power asymmetry [62].…”
Section: Conceptual Modelmentioning
confidence: 99%